INSULIN ANTIBODY MEASUREMENTS: SHEDDING LIGHT ON HIRATA’S DISEASE - Apparow, Saraswathy; Tong, Chin Voon; Low, Chee Koon; Wong, Hui Chin; Yong, Liang (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The Endocrine Society Clinical Practice Guideline recommends measurement of insulin autoantibodies (IAA) upon confirmation of endogenous hyperinsulinism. The differential diagnosis of endogenous hyperinsulinism include insulinoma, post-bariatric hypoglycaemia, nesidioblastosis and insulin autoimmune syndrome (IAS). IAS, also known as Hirata's disease, is a rare immunemediated disorder characterised by hyperinsulinaemic hypoglycaemic episodes. It is increasingly being recognized in Malaysia because of accessibility to IAA testing. CASE We describe two cases of newly diagnosed IAS with varied clinical presentations and treatment approaches. The first patient is a 57-year-old male with Graves’ disease who experienced severe and recurrent hypoglycaemia during fasting and postprandial states. The second patient is a 56-year-old female with hypertension and bronchial asthma who developed recurrent hypoglycaemia despite cessation of insulin therapy following the treatment for severe refractory diabetic ketoacidosis. Laboratory findings for both patients showed elevated serum insulin and C-peptide during the hypoglycaemic event, with insulin/C-peptide ratio >1. Pancreatic antibodies were negative. Serum insulin autoantibodies measured on chemiluminescent immunoassay revealed remarkably high titres in both cases. Triggering factors were identifiable in both cases: in the first, exposure to carbimazole; and in the second patient: exposure to pantoprazole, amlodipine, metoprolol, perindopril and amoxicillin clavulanate. The first patient improved with dietary modification and alphaglucosidase inhibitor. The second patient was treated with steroids. CONCLUSION Our case series highlighted the importance of measuring insulin antibody titer after confirming endogenous hyperinsulinism. High insulin concentration along with insulin/C-peptide molar ratio >1 should raise the clinical suspicion of IAS. Early recognition of this syndrome can avoid the need for laborious and costly investigation of presumed insulinoma with appropriate therapeutic approach.